Sexuality after surgery for diffuse low-grade glioma - Surbeck, Werner (Neuro Oncol, 2015)
BACKGROUND: Although neurological and neurocognitive outcomes have previously been studied after resection of diffuse low-grade glioma (DLGG), the impact of surgery on sexual life has not been investigated. Our aim was to assess whether DLGG surgery could have consequences on sexual experience. METHODS: Anonymous standardized questionnaires concerning sexual functioning, including the Arizona Sexual Experiences Scale (ASEX) and a subjective statement, were completed by 32 patients who underwent surgery for DLGG. All patients returned to a normal social and professional life following resection, with neither neurological deficits nor depression. No radiotherapy was administered, and patients who received chemotherapy were without treatment for at least 1 year. RESULTS: Seventeen patients (53%) reported a postoperative sexual change, with subjective deterioration in 15 (88%) and improvement in 2 (12%). Sexual dysfunction according to ASEX affected 9 of 15 women (60%) and 5 of 17 men (29%). Right-sided resections were associated with more difficulties in reaching orgasm than left-sided resections (P < .02). Men with temporal lobe resection displayed more reduction in sexual drive (P < .003) and sexual arousal (P < .004) than women, resulting in significant higher overall ASEX scores for temporal lobe resections in men (P = .01). Men remaining on antiepileptic drugs who underwent right-sided resection displayed higher overall ASEX scores than women (P = .031). CONCLUSIONS: This first evaluation of sexual life after surgery for DLGG suggests that sexual dysfunction is common in this population. Therefore, we suggest that sexual health should consistently be addressed during routine pre- and postoperative examination of patients with DLGG.